Performance of laminated contact material Cu—Mo in open air AC low voltage contactors - Miedzinsk, i B.; Wojtas, P.; Kozłowski, A.; Wosik, J.; Grodzinski, A.; Habrych, M.; Grechanyuk, N. (Электрические контакты и электроды, 2014)
In the paper performance of laminated contact material Cu—Mo when use in open air ac low voltage contactors is presented and discussed. On the basis of the investigated results conclusions on effective application of such material to replace silver based compositions are formulated.